Unimolecular and water reactions of oxygenated and unsaturated Criegee intermediates under atmospheric conditions. Issue 11 (4th March 2022) - Vereecken, L.; Novelli, A.; Kiendler-Scharr, A.; Wahner, A.
Abstract : Theoretical kinetic data is used to update structure–activity relationships for Criegee intermediates, including fast reactions for intramolecular insertion in oxygenated SCI. Abstract : Ozonolysis of unsaturated hydrocarbons (VOCs) is one of the main oxidation processes in the atmosphere. The stabilized Criegee intermediates (SCI) formed are highly reactive oxygenated species that potentially influence the HOx, NOx and SOx cycles, and affect aerosol formation by yielding low-volatility oxygenated compounds. The current knowledge spans mostly SCI formed from primary emitted VOCs, but little is known about the reactivity of oxygenated SCI. In this work we present a theoretical kinetic study of a large number of unsaturated and oxygenated SCI, covering CC, OH, OR, OOH, OOOH, COOH, COOR, and ONO2 functionalities at various stereo- and site-specific substitutions relative to the SCI carbonyl oxide moiety. Several novel reaction types are covered, the most important of which are fast intramolecular insertion reactions in OH, OOH and COOH groups, or secondary ozonide formation with a COOH group, forming cyclic oxygenated species; these reaction classes are reminiscent of the analogous bimolecular reactions. The reaction with H2 O molecules was likewise studied, finding that these cyclisation reactions can be catalysed, with predicted rate coefficients nearing the collision limit. The theoretical data is used to extend the structure–activity relationships (SARs) proposed by Vereecken et al. (2017), predicting the dominant unimolecular reaction class and rate, and the rates for reaction with H2 O and (H2 O)2 . The SARs cover over 300 SCI categories with over 40 substituent categories. The validation of these SARs is discussed, and an outlook is given for further improvement. The generally short lifetime of oxygenated SCI suggests that ozonolysis of secondary, oxygenated VOCs is unlikely to yield ambient concentrations of SCI exceeding 10 4 cm −3 but will contribute strongly to the in situ formation of oxygenated VOCs.